PENGEMBANGAN KOMPETENSI PROFESIONAL GURU MENGGUNAKAN METODE WORKSHOP UNTUK MENINGKATKAN MUTU PEMBELAJARAN DI SDN 3 ALIYAN - Eka Afrida Ermawati; Siska Aprilia Hardiyanti; Aprilia Divi Yustita; Tri Maryono Rusadi (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
SDN 3 Aliyan is an elementary school located in RT.03 RW.02 Aliyan Village, Rogojampi District, Banyuwangi Regency. The physical condition of this school is improper because some classes are put in the same room which is only separated using a board. Even the total number of students in this school is only 36 students. Not only improper condition of the physical condition of the school, but human resources in this school is also limited. Thus, many incompetent teachers have to teach subjects that they are not mastered. The absence of the government in solving this problem makes the researchers eager to conduct an activity that can improve the professional competence of the teachers there. This activity is a form of dedication from the Banyuwangi State Polytechnic which aims to improve the professional abilities of teachers at SDN 3 Aliyan. This activity is carried out through workshops on mathematics subjects and training for teachers in making learning media. It is hoped that after this activity is carried out, the competence of teachers in this school will increase, especially in mathematics, so that the teaching and learning process will be better. After the activity is finished, the researcher will continue to observe the results of the program by visiting schools at certain times. This is done so that what has been taught to the teachers can continue to be applied in the next learning process